Directions of Efficiency Research for Biotronics Technologies - Balaišis, P.; Gužauskas, R.; Eidukas, D.; Valinevičius, A. (Elektronika ir Elektrotechnika, 2009)
The direction of efficiency research was formulated for biotronics technologies. Distinctiveness of integrated biotronics systems was emphasized in comparison to the other integrated biological and electronic systems. Directions of efficiency research of biotronics systems were formulated and research tasks were formed. The conception of phytotronic cybernetics was offered. Composition of technologies of phytotronic cybernetics was illustrated, directions of efficiency research of these technologies were provided. A conception of informatics of phytotronic cybernetics technologies was offered, peculiarities of information detection, storage and efficiency evaluation of these technologies were demonstrated. It is offered to consider the features of dynamic information, reliability of its sources, data transmission methods, etc. Several directions for the future research were offered. Ill. 5, bibl. 6 (in English; abstracts in English, Russian and Lithuanian).